Client Experiences in a Mobile-Phone Counseling Intervention for Enhancing Access to Prevention of Mother To-Child Transmission (PMTCT) Services in Kenya - Okal, Jerry Okoth; Sarna, Avina; Lango, Daniel; Matheka, James; Owuor, Danmark; Kinywa, Eunice Auma; Kalibala, Sam (Frontiers in Global Women's Health, 2022)
Background: The prevention of mother-to-child transmission (PMTCT) is considered one of the most successful HIV prevention strategies in reducing HIV acquisition in utero or at birth. It is anticipated that with the exponential growth of digital technologies mobile phones can be utilized to enhance PMTCT services by improving provider-client interactions, expanding access to counseling services, and assisting in counteracting social and structural barriers to uptake of PMTCT services. Understanding the subjective experiences of women accessing PMTCT services in different settings has the potential to inform the development and promotion of such methods. This paper explores the perspectives of HIV-positive pregnant women attending maternal and neonatal clinic services in Kisumu, Kenya. Methods: Data are reported from in-depth interviews with women and men, following a longitudinal study investigating the impact of a structured, counselor-delivered, cell phone counseling intervention to promote retention in care and adherence to ARV prophylaxis/treatment, for HIV-positive pregnant women. Thematic content analysis was conducted. Results: Discussions indicated that cell-phone counseling provided useful health-related information, enhanced agency, and assisted mothers access critical PMTCT services across the cascade of care. Similarly, cell-phone counseling offered personalized one-to-one contact with trained health providers including facilitating discussion of personal issues that likely affect access to services. Findings also identified barriers to the uptake of services, including a lack of partner support, poor health, poverty, facility-related factors, and provider attitudes. Discussion: Overall, findings show that cell-phone counseling is feasible, acceptable, and can enhance access to PMTCT services by overcoming some of the individual and facility-level barriers. Although cell-phone counseling has not been routinized in most health facilities, future work is needed to assess whether cell-phone counseling can be scaled up to aid in the effective use of HIV and PMTCT services as well as improving outcomes for mother and child dyad.